2019
DOI: 10.1037/emo0000535
|View full text |Cite
|
Sign up to set email alerts
|

Does repetitive negative thinking affect attention? Differential effects of worry and rumination on attention to emotional stimuli.

Abstract: Worry and rumination, two cardinal responses to emotional events, are key for maintaining negative emotion and have been implicated in the etiology and maintenance of anxiety and depressive disorders. Though worry and rumination are highly correlated with one another and people who engage in one often engage in both, they may differentially affect emotion. Specifically, previous work suggests that worry helps people avoid (intense) emotion, while rumination provokes it. Examining the ways in which these two fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Additionally, it is not clear if the ER task we used is the best way to measure visual attention towards emotional stimuli. In fact, despite the advantage in ecological validity to use dynamic faces over static ones, some recent studies have used negative and positive images to measure visual attention in clinical cohorts, including the recent Lewis et al [10] study that influenced our study hypotheses. Moreover, despite their potential advantage in ecological validity, traditional ER tasks are riddled with measurement constraints such as ceiling effects for happiness and response bias [39][40][41].…”
Section: Anxiety But Not Social Anxiety and Attention To The Mouthmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is not clear if the ER task we used is the best way to measure visual attention towards emotional stimuli. In fact, despite the advantage in ecological validity to use dynamic faces over static ones, some recent studies have used negative and positive images to measure visual attention in clinical cohorts, including the recent Lewis et al [10] study that influenced our study hypotheses. Moreover, despite their potential advantage in ecological validity, traditional ER tasks are riddled with measurement constraints such as ceiling effects for happiness and response bias [39][40][41].…”
Section: Anxiety But Not Social Anxiety and Attention To The Mouthmentioning
confidence: 99%
“…In general, individuals with anxiety disorders show increased vigilance to threat during free viewing and visual search and difficulty disengaging from threat during visual search but not during free viewing tasks relative to controls [ 1 ]. Recent work has examined the relations between worry, rumination, and visual attention, and found that self-reported rumination is linked to greater attention to sad stimuli [ 8 , 9 ] but worry, compared with rumination, leads to relative avoidance of positive information [ 10 ]. Whether this is true across anxiety disorders, representing a transdiagnostic process, remains to be tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonreactivity, on the other hand, is the ability to tolerate potentially distressing thoughts and emotions without feeling compelled to react to them (e.g., by trying to avoid or change them). According to several prominent theoretical models of worry, worry functions primarily as a (generally maladaptive) strategy for controlling or changing one's emotional experiences; for example, to avoid distressing mental imagery (Borkovec, Alcaine, & Behar, 2004), positive emotional stimuli (Lewis et al, 2019), or a negative emotional contrast (Newman & Llera, 2011). If these models are correct, they would most likely predict a specific inverse relationship between worry severity and nonreactivity.…”
Section: Facets Of Mindfulness and Ptmentioning
confidence: 99%
“…At study visit, participants received an adaptation of a well-studied induction procedure (e.g., Lewis, Blanco, Raila, & Joormann, 2019;Nolen-Hoeksema & Morrow, 1993). This entailed exposing participants to cues designed to induce either a ruminative (RUM) or a neutral (NEU) state.…”
Section: Rumination and Neutral Inductionmentioning
confidence: 99%